2020
DOI: 10.3390/su12093865
|View full text |Cite
|
Sign up to set email alerts
|

Does Gender Diversity Influence Business Efficiency? An Analysis from the Social Perspective of CSR

Abstract: Gender-related corporate social responsibility (CSR) practices are receiving increasing attention from all stakeholders, as the commitment to achieving equal opportunities for women has become a top priority. However, the reality is that women remain under-represented at the most senior corporate level, and there is a lack of knowledge about many of the implications this situation entails. This study aimed to provide the first analysis of the direct effect and the indirect effect (through leverage) of board ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 75 publications
(182 reference statements)
1
9
0
1
Order By: Relevance
“…Assenga et al (2018), Blibech and Berraies (2018) and Naseem et al (2020) found that the CEO duality exhibits a significant negative association with firm performance. Regarding the female directors' impact on firm financial performance, previous studies (Pucheta -Martínez and Gallego-Álvarez, 2020;Martínez and Rambaud, 2019;Gutiérrez-Fern andez and Fern andez-Torres, 2020) found that women on the board are positively related with financial performance. They indicate that female presence on boards, as a key resource, plays an important role in providing a shared vision of the future to promote the firm profitability and value ( -Dặng et al, 2020).…”
Section: Ceo-duality and Corporate Social Responsibilitymentioning
confidence: 96%
See 1 more Smart Citation
“…Assenga et al (2018), Blibech and Berraies (2018) and Naseem et al (2020) found that the CEO duality exhibits a significant negative association with firm performance. Regarding the female directors' impact on firm financial performance, previous studies (Pucheta -Martínez and Gallego-Álvarez, 2020;Martínez and Rambaud, 2019;Gutiérrez-Fern andez and Fern andez-Torres, 2020) found that women on the board are positively related with financial performance. They indicate that female presence on boards, as a key resource, plays an important role in providing a shared vision of the future to promote the firm profitability and value ( -Dặng et al, 2020).…”
Section: Ceo-duality and Corporate Social Responsibilitymentioning
confidence: 96%
“…representation was assessed by calculating the percentage female directors serving on a firm's board. We calculate the ratio of female board members to total board members of the sampled firms (Kachouri et al, 2020;Gutiérrez-Fern andez and Fern andez-Torres, 2020;Liu et al, 2020). CEO-Chair duality was measured as dummy variable equaling 1 if the CEO is also chairman of the board of directors, or zero otherwise (Alabdullah et al, 2019;Endrikat et al, 2020).…”
Section: Corporate Social Responsibilitymentioning
confidence: 99%
“…For this reason, it is necessary to establish a theoretical framework on what gender equality policies are without entering into conflict, since the objective is to demonstrate that their disclosure is not only positive because it reduces inequalities, but because it also has an impact on the company's performance. In addition, this research aims to demonstrate the impact of these policies at all hierarchical levels in the company, and not only on management positions, which the previous literature analyses to a greater extent ( Ekadah and Kiweu, 2012 ; Baixauli-Soler et al., 2016 ; Cucari et al., 2017 ; Romano et al., 2020 ; Gutiérrez-Fernández and Fernández-Torres, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…First, this analysis contributes to the available literature on CSR from employees' perspectives. Most of the available literature has investigated CSR to achieve other organization-related outcomes including organizational performance [45][46][47], organizational efficiency [48,49], organizational reputation [50]. However, the relationship of CSR with employee behavior is relatively new to the literature.…”
Section: Introductionmentioning
confidence: 99%